2017
DOI: 10.1038/s41598-017-16394-2
|View full text |Cite|
|
Sign up to set email alerts
|

The responses of cancer cells to PLK1 inhibitors reveal a novel protective role for p53 in maintaining centrosome separation

Abstract: Polo-like kinase-1 (PLK1) plays a major role in driving mitotic events, including centrosome disjunction and separation, and is frequently over-expressed in human cancers. PLK1 inhibition is a promising therapeutic strategy and works by arresting cells in mitosis due to monopolar spindles. The p53 tumour suppressor protein is a short-lived transcription factor that can inhibit the growth, or stimulate the death, of developing cancer cells. Curiously, although p53 normally acts in an anti-cancer capacity, it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…We found that p53 loss prevented vincristine-induced H2AX phosphorylation, PARP cleavage and mutagenesis. The observation that p53 deficiency reduced vincristine-induced mutagenesis and H2AX phosphorylation, but ATM loss did not, suggests that activation of p53 (and the ensuing caspase-dependent DNA damage and mutations) is not solely accomplished by ATM under these conditions, consistent with previous reports linking ATR to p53 activation when mitosis is perturbed 88 . Suppressing NHEJ, through genetic or pharmacological targeting of DNA-PKcs, significantly reduced the frequency of HPRT mutations in vincristine-treated cells, but reducing homologous recombination failed to significantly impinge on vincristine-induced death or mutagenesis.…”
Section: Discussionsupporting
confidence: 90%
“…We found that p53 loss prevented vincristine-induced H2AX phosphorylation, PARP cleavage and mutagenesis. The observation that p53 deficiency reduced vincristine-induced mutagenesis and H2AX phosphorylation, but ATM loss did not, suggests that activation of p53 (and the ensuing caspase-dependent DNA damage and mutations) is not solely accomplished by ATM under these conditions, consistent with previous reports linking ATR to p53 activation when mitosis is perturbed 88 . Suppressing NHEJ, through genetic or pharmacological targeting of DNA-PKcs, significantly reduced the frequency of HPRT mutations in vincristine-treated cells, but reducing homologous recombination failed to significantly impinge on vincristine-induced death or mutagenesis.…”
Section: Discussionsupporting
confidence: 90%
“…[86] It is important to note, however, that functional p53 reduces cell sensitivity to PLK1 inhibitors by permitting centrosome separation and activating DNA damage response enzymes, ATM and ATR (discussed in Section 4.5), following p53 phosphorylation at the key regulatory site, Ser15. [88] Although TP53 mutations are rare in H3.1K27M DIPG tumors, the H3.1 DIPG cells used by Amani et al [86] (SU-DIPG-IV) [46] also harbor somatic mutations in ACVR1 and MDM4, with MDM4 known to inhibit p53 by binding to its transcriptional activation domain. In an in vitro setting, the treatment of these SU-DIPG-IV cells with volasertib led to increased phosphorylation of γ H2AX, decreased cell proliferation, and increased apoptosis.…”
Section: Serine/threonine-protein Kinase Plk1mentioning
confidence: 99%
“…In vitro analysis revealed significant G2‐to‐M‐phase cell cycle arrest, with H3.1K27M mutant DIPG cell lines showing more than a twofold increased sensitivity to volasertib than H3.3K27M mutant cells . It is important to note, however, that functional p53 reduces cell sensitivity to PLK1 inhibitors by permitting centrosome separation and activating DNA damage response enzymes, ATM and ATR (discussed in Section 4.5), following p53 phosphorylation at the key regulatory site, Ser15 . Although TP53 mutations are rare in H3.1K27M DIPG tumors, the H3.1 DIPG cells used by Amani et al .…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%
“…We identified Polo-like kinase 1 (PLK1) as a direct target of miR-505. Earlier evaluations have revealed that PLK1 has a major part in regulating DNA synthesis,15 p53 transactivation,16 as well as tumor cell metastasis 17. So we hypothesized that miR-505 suppressed EMT progress probably through PLK1 molecules.…”
Section: Resultsmentioning
confidence: 89%